2020
DOI: 10.18203/2349-3259.ijct20201711
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effect of zinc gluconate and placebo in the treatment of tachypnea, dyspnea and fever in children aged 2 to 23 months with acute bronchiolitis

Abstract: <p class="abstract"><strong>Background:</strong> Acute viral bronchiolitis is the most common infection of the lower respiratory tract in infants under 2 years and is one of the reasons for their admission all around the world. The aim of this study was comparing the effect of zinc gluconate and placebo in the treatment of tachypnea, dyspnea and fever in children aged 2 to 23 months with acute bronchiolitis.</p><p class="abstract"><strong>Methods:</strong> This randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Two RCTs evaluated the effect of zinc on bronchiolitis in children under two years 34,35 . Ahadi et al found that children in the treatment group had shorter hospital LOS (4.14 ± 1.21 versus 4.64 ± 1.2 days; p=0.016) and less wheezing and rhinorrhea at 72 hours (16% vs 36%, p=0.023, 0 vs 12%, p=0.027, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Two RCTs evaluated the effect of zinc on bronchiolitis in children under two years 34,35 . Ahadi et al found that children in the treatment group had shorter hospital LOS (4.14 ± 1.21 versus 4.64 ± 1.2 days; p=0.016) and less wheezing and rhinorrhea at 72 hours (16% vs 36%, p=0.023, 0 vs 12%, p=0.027, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Two RCTs evaluated the effect of zinc on bronchiolitis in children under two years [ 73 , 74 ]. Ahadi et al [ 73 ] found that children in the treatment group had shorter mean hospital LOS (4.14 (standard deviation (SD) = 1.21) vs 4.64 (SD = 1.2) days; P = 0.016) and less wheezing and rhinorrhoea at 72 hours (16% vs 36%, P = 0.023, 0 vs 12%, P = 0.027, respectively). Both found no difference in tachypnoea, retractions, or cyanosis at 24 hours in the treatment vs control group; both studies were deemed to have high risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…11 Another study by Ahadi ,Mirzarahimiand Barakshowed that the use of zinc gluconate as a zinc supplement in infants with acute bronchiolitis could improve tachypnoea, dyspnoea and fever in children aged 2 to 23 months with acute bronchiolitis and decrease the duration of hospitalization. 12 The findings of some of the above studies are somewhat contradictory. If zinc can be successfully used in the treatment of acute bronchiolitis, then it may not only help to reduce morbidity but also reduce future episodes of wheezing in children.…”
Section: Discussionmentioning
confidence: 98%